2016
DOI: 10.1021/acs.jmedchem.6b00064
|View full text |Cite|
|
Sign up to set email alerts
|

Discovery of Entrectinib: A New 3-Aminoindazole As a Potent Anaplastic Lymphoma Kinase (ALK), c-ros Oncogene 1 Kinase (ROS1), and Pan-Tropomyosin Receptor Kinases (Pan-TRKs) inhibitor

Abstract: Anaplastic lymphoma kinase (ALK) is a receptor tyrosine kinase responsible for the development of different tumor types. Despite the remarkable clinical activity of crizotinib (Xalkori), the first ALK inhibitor approved in 2011, the emergence of resistance mutations and of brain metastases frequently causes relapse in patients. Within our ALK drug discovery program, we identified compound 1, a novel 3-aminoindazole active on ALK in biochemical and in cellular assays. Its optimization led to compound 2 (entrect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
160
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(174 citation statements)
references
References 46 publications
5
160
1
1
Order By: Relevance
“…Using the Entrectinib:ALK structure (5FTO) as a model of active site inhibitors, we can also predict other residues that, when mutated, could affect our compounds within the new binding site (33). We predict four residues-Phe-589, Gly-667, Asp-668, and Phe-669-by identifying residues within 5 Å of both Entrectinib and compound 1 in TrkA.…”
Section: Discussionmentioning
confidence: 99%
“…Using the Entrectinib:ALK structure (5FTO) as a model of active site inhibitors, we can also predict other residues that, when mutated, could affect our compounds within the new binding site (33). We predict four residues-Phe-589, Gly-667, Asp-668, and Phe-669-by identifying residues within 5 Å of both Entrectinib and compound 1 in TrkA.…”
Section: Discussionmentioning
confidence: 99%
“…Entrectinib inhibits TRK in addition to ROS1 and ALK (132, 133). Updated results from a phase I study of entrectinib showed significant responses in TKI-naïve patients with NTRK -, ROS1 -, and ALK1 -rearranged solid tumors (confirmed ORR of 100%, 86%, and 57%, respectively) (134).…”
Section: Developing Strategies To Overcome Resistancementioning
confidence: 99%
“…Entrectinib is an oral inhibitor with low nanomolar potency against ALK, ROS1, and TRK kinases in enzymatic assays (85), and is able to effectively penetrate the blood-brain barrier (86). Its cellular IC 50 against ROS1 in Ba/F3 models is ~5 nM (86).…”
Section: Ros1-targeted Therapies In Lung Cancermentioning
confidence: 99%